Utilization of hydrobionts biomass to increase the efficiency of biological treatment of surface water - Pogrebnaya Irina; Mikhailova Svetlana (BIO Web of Conferences)
The article deals with the actual scientific and practical problem of improving the ecological state of the hydrosphere through the use of wastewater and surface water treatment methods from hydrobionts. The paper describes the cleaning technology in areas inhabited by a certain type of hydrobionts (freshwater organisms), in the process of sequential passage of the polluted water environment through these areas. At the same time, at all stages of purification by hydrobionts, which are components of biological technology, excess biomass is formed. The biomass obtained during the cleaning process must be removed and disposed of. The utilization of accumulated hydrobiont biomass in wastewater and surface water treatment technologies discussed in the study has found its application in agriculture in the form of animal feed as compost, as well as in agricultural technology as raw materials for the production of organic or mineral fertilizers. It is proposed to technologically integrate wastewater and surface water treatment by colonizing reservoirs with various types of hydrobionts: anaerobic bacteria, aerobic microorganisms (oligotrophs, protozoa), filter-feeding hydrobionts, and predators. These artificially created biocenoses mimic the environment. The authors describe the process of studying the concentration of microalgae using electric current, including the process of collecting accumulated biomass of macroalgae, aquatic plants, and plants of artificially created wetlands. The life cycle of hydrobionts is analyzed, and the features of using various types of hydrobionts in the technology of cleaning polluted water environments are studied. The process of rehabilitation of a water body was considered on the example of Lake Tikhoe, located in the city of Tyumen.